Competition, productivity and prices in the euro area services sector - Ad van Riet; Moreno Roma (European Central Bank (ECB), 2006)
This paper analyses the degree of competition in the euro area services sector and its effects on labour productivity and relative prices in that sector over the period 1980-2003. The importance of the euro area services sector has significantly increased over time; it now accounts for around 70% of the euro area's total nominal value added and employment. Labour productivity growth across the euro area services industries appears to be characterised by a high degree of diversity and the level of services inflation is on average higher than aggregate inflation. Investigating several proxies of market competition for the non-financial business services, the paper finds that limited competition in services tends to hamper labour productivity growth in the services sector. Moreover, results tend to suggest that measures aimed at increasing services market competition may have a dampening impact on relative price changes in some services sectors and thus temporarily on aggregate inflation.
Keywords: 330; Dienstleistungssektor; Wettbewerb; Marktstruktur; Arbeitsproduktivität; Verbraucherpreisindex; EU-Staaten